The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.14576
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy can induce weight normalization of morbidly obese mice despite undiminished ingestion of high fat diet

Abstract: Morbidly obese patients who accomplish substantial weight loss often display a long-term decline in their resting metabolism, causing even relatively restrained caloric intake to trigger a relapse to the obese state. Paradoxically, we observed that morbidly obese mice receiving chemotherapy for cancer experienced spontaneous weight reduction despite unabated ingestion of their high fat diet (HFD). This response to chemotherapy could also be achieved in morbidly obese mice without cancer. Optimally dosed methot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…In the groups where Maca at 500 mg/kg (Figures 5e and 6e) and 1,000 mg/ kg (Figures 5f and 6f) alone were administered, the histology of the testis was normal and well preserved, with features characteristic of tubules at the later phase of stage of XII; showing a row of mature primary spermatocytes and elongated spermatids with fewer intermediate germ cells (round spermatid) observed, and numerous elongated spermatids whose tails radiate into the tubular lumen. Table 3 shows In this study, administration of cyclophosphamide was associated with significant weight loss, which is consistent with reports of previous studies in rodents (Kanno, Sensiate, Aparecida de Paula, & Salles, 2009;Kumar, Singh, & Reddy, 2013;Latha & Panikkar, 1999;Myers et al, 2017). Weight loss is a common side-effect of cyclophosphamide therapy.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter supporting
confidence: 92%
See 2 more Smart Citations
“…In the groups where Maca at 500 mg/kg (Figures 5e and 6e) and 1,000 mg/ kg (Figures 5f and 6f) alone were administered, the histology of the testis was normal and well preserved, with features characteristic of tubules at the later phase of stage of XII; showing a row of mature primary spermatocytes and elongated spermatids with fewer intermediate germ cells (round spermatid) observed, and numerous elongated spermatids whose tails radiate into the tubular lumen. Table 3 shows In this study, administration of cyclophosphamide was associated with significant weight loss, which is consistent with reports of previous studies in rodents (Kanno, Sensiate, Aparecida de Paula, & Salles, 2009;Kumar, Singh, & Reddy, 2013;Latha & Panikkar, 1999;Myers et al, 2017). Weight loss is a common side-effect of cyclophosphamide therapy.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter supporting
confidence: 92%
“…Figures 3c and 4c), there was minimal swelling and cellular debris; and the duct epithelium and cells were better preserved, compared to the cyclophosphamide-only group. There was also loss of interstitial space between In this study, administration of cyclophosphamide was associated with significant weight loss, which is consistent with reports of previous studies in rodents (Kanno, Sensiate, Aparecida de Paula, & Salles, 2009;Kumar, Singh, & Reddy, 2013;Latha & Panikkar, 1999;Myers et al, 2017). In the group where Maca alone was administered at 500 mg/kg (Figures 3e and 4e), there was an increase in sperm concentration within the ducts; duct epithelium and cells were normal and well preserved.…”
Section: Effect Of Maca On Latency To Achieve Pregnancy and Litter supporting
confidence: 91%
See 1 more Smart Citation
“…BMI class change from normal to underweight was higher for gastrointestinal than other malignancies ( 24 ; 27 ). In a recent report, certain chemotherapeutic agents may cause weight loss in obese mice by depleting stores of adipocytes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that MTX can ameliorate diet-induced insulin resistance and inflammation ( DeOliveira et al, 2012 ; Myers et al, 2017 ), although the mechanisms remained poorly understood. To evaluate the effective dose of MTX on Mir181b expression in vivo, C57Bl6 mice were injected with 0.5 mg/kg or 1.0 mg/kg of MTX.…”
Section: Resultsmentioning
confidence: 99%